Perinatal Androgenic Exposure and Reproductive Health Effects Female Rat Offspring - Guerra, Marina T.; Silva, Raquel F. [UNESP]; Luchiari, Heloise R. [UNESP]; Sanabria, Marciana [UNESP]; Kempinas, Wilma De Grava [UNESP] (Taylor & Francis Inc, 2014)
Environmental contaminants known as endocrine-disrupting chemicals (EDC) have been associated with adverse effects on reproductive processes. These chemicals may mimic or antagonize endogenous hormones, disrupting reproductive functions. Although preliminary studies focused on environmental estrogens, the presence of compounds with androgenic activity has also been described. This study examines exposure of female pregnant and lactating rats to low doses of androgens and assesses potential effects on female offspring. Pregnant Wistar rats were exposed to testosterone propionate (TP) at doses of 0.05, 0.1, or 0.2 mg/kg or corn oil (vehicle), subcutaneously, to determine influence on reproductive health of female offspring. There were two exposure groups: (1) rats treated from gestational day (GD) 12 until GD 20; and (2) animals treated from GD 12 until the end of lactation. Perinatal exposure to TP produced increased anogenital distance after birth and diminished height of uterine glandular epithelium at puberty in animals exposed to 0.2 mg/kg. However, these alterations were not sufficient to impair sexual differentiation and normal physiology of the female rat reproductive tract.